2019
DOI: 10.3390/fib7100083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spinning Temperature and Filler Content on the Properties of Melt-Spun Soy Flour/Polypropylene Fibers

Abstract: Polypropylene (PP) fibers are heavily used in disposable nonwovens fabrics because of their desirable properties and low-cost, but they are not biodegradable. With the goal of reducing non-biodegradable plastic waste in the environment, the primary aim of this study was to produce fibers with reduced content of PP for disposable fabrics by incorporating soy flour, a bio-based renewable material. An optimum processing temperature of 190 °C was established, and thin fibers with a diameter under 60 µm were succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…It is postulated that such surface condition occurred due to the partial dispersion of curcumin particles in the PLA/PPC blend. A similar textured or bead-like surface effect was also obtained for melt-spun fibers from the polypropylene/soy particle blend [51] and the polypropylene/talc blend [52]. Contrary to the perception that such textured surface is undesirable, this bead-like surface is actually a unique feature because it imitates the tactile feel of the irregular cross-section and highly crenulated structure of natural fibers such as those found in cotton [51].…”
Section: Fiber Morphologysupporting
confidence: 57%
“…It is postulated that such surface condition occurred due to the partial dispersion of curcumin particles in the PLA/PPC blend. A similar textured or bead-like surface effect was also obtained for melt-spun fibers from the polypropylene/soy particle blend [51] and the polypropylene/talc blend [52]. Contrary to the perception that such textured surface is undesirable, this bead-like surface is actually a unique feature because it imitates the tactile feel of the irregular cross-section and highly crenulated structure of natural fibers such as those found in cotton [51].…”
Section: Fiber Morphologysupporting
confidence: 57%
“…The filter membrane exhibited a high efficiency of 99.3% and compared to a 3M respirator, still exhibits a 15% improvement in quality factor after 6 hours of filtration time [ 343 ]. Guzdemir and Ogale recently reported producing fibres with reduced content of PP for disposable fabrics by incorporating bio-based renewable material, soy flour, where thin fibres with a diameter under 60 μ m can be successfully melt-spun [ 344 ]. It was found that the presence of soy particulates on fibre surface enhanced its water absorption and colourability properties while retaining the feel of natural fibres.…”
Section: Future Perspectivementioning
confidence: 99%
“…Compounding soy flour with petroleum-based thermoplastic polymers like polyethylene (PE), polypropylene (PP), and poly(lactic acid) (PLA) is another strategy to melt spin soy-based fibers [124,125]. Soy flour, containing 53% protein and up to 30% carbohydrate, is a cost-effective alternative to SPI and SPC [56,124].…”
Section: Melt Spinningmentioning
confidence: 99%
“…Compounding soy flour with petroleum-based thermoplastic polymers like polyethylene (PE), polypropylene (PP), and poly(lactic acid) (PLA) is another strategy to melt spin soy-based fibers [124,125]. Soy flour, containing 53% protein and up to 30% carbohydrate, is a cost-effective alternative to SPI and SPC [56,124]. However, poor interfacial adhesion between hydrophilic soy flour and nonpolar thermoplastic polymers leads to soy flour agglomeration, high melt viscosity, and interphase discontinuities.…”
Section: Melt Spinningmentioning
confidence: 99%